2012
DOI: 10.1016/j.yebeh.2011.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the chronic use of benzodiazepines prescribed for seizure control on the anxiety levels of patients with epilepsy

Abstract: In a cross-sectional study, we evaluated the impact of the chronic use of benzodiazepines (BDZ) prescribed for seizure control on the anxiety levels of patients with temporal lobe epilepsy. We assessed the anxiety level of 99 patients with temporal lobe epilepsy with (n=15) or without (n=84) BDZ for seizure control, using the Beck Anxiety Inventory (BAI) or the Hamilton Anxiety Scale (HAMA). Independent risk factors for high anxiety levels were being a female patient (O.R.=2.93; 95% C.I.=1.05-8.16; p=0.039), h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…They are, however, only treatment option of further choice in epilepsy. Dal Pizzol et al found similar anxiety levels in patients with and without BZD administered for epilepsy (Pizzol et al, 2012). This may, however, be due to the fact that the anxiety levels were not examined before initiation of BZD so that there is no baseline examination.…”
Section: Drugsmentioning
confidence: 99%
“…They are, however, only treatment option of further choice in epilepsy. Dal Pizzol et al found similar anxiety levels in patients with and without BZD administered for epilepsy (Pizzol et al, 2012). This may, however, be due to the fact that the anxiety levels were not examined before initiation of BZD so that there is no baseline examination.…”
Section: Drugsmentioning
confidence: 99%